Policy for Media School Activity for the Youth in the Gedeg Village Community - Sang Ayu Putu Rahayu; Anisa Faraditha Nanda Sari; Amelia Aghata; Said Noor Rahman (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2022)
Universitas Negeri Semarang (UNNES) as a state university organizes community services (KKN) in the form of UNNES GIAT. During the implementation of UNNES GIAT in Gedeg Village, one of the problems found was the lack of education and knowledge levels. Based on the problems faced, policies are needed to improve education and knowledge, one of which is by providing Graphic Design Training. Students conduct workshops and educational assistance through media schools as an effort to solve problems in the field of graphic design, especially the younger generation group in Gedeg Village, namely IPNU and IPPNU. From the results of the activity it was found that the participants were very enthusiastic and fully accepted the material provided, from this it indicated that the activity was successful. In the end, special policies need to be made for schools in Gedeg in order to improve the quality of education from the perspective of technological progress, namely media schools.